P30 Can non-allergy health workers safely delabel reported penicillin allergies using an antibiotic allergy assessment tool? - A multicentre study. (8th April 2021) - Owens, Rhys; Sandoe, Jonathan; Whyte, Andrew; West, Robert; Slatter, Mandy; Stonell, Rebecca; Powell, Neil; Owens, Rhys
Abstract: Background: False penicillin allergy labels can be potentially hazardous to patients. Most penicillin allergy labels can be safely removed following risk stratification and formal drug challenge. These de-labelling strategies have been limited to specialist allergy and infectious disease services. Aims: To determine whether non-allergy specialist health-care workers can use an antibiotic allergy assessment tool (AAAT) to correctly phenotype and manage reported penicillin allergy. Method: Non-allergy health-care workers in three UK hospital were emailed online questionnaires and asked to assign the allergy phenotype and management recommendation for eight vignettes of real cases reporting a penicillin allergy using the AAAT. In one hospital participants were randomised into two groups: one group was directed to use the AAAT whilst the second group had no decision tool. Participants were assigned an average score for correct allergy phenotype, management and a major error rate. Results: Use of the AAAT across the eight vignettes significantly improved the average score for assigning correct phenotype (6.7 vs 5.2 p < 0.001), management choice (7.1 vs 5.7 p < 0.001), and major error rate (0.6 vs 1.6 p < 0.001). Participant performance with the AAAT was generalizable across all three hospitals. Despite use of the AAAT 35-40% of participants made at least one major error. Conclusion: The AAAT significantly improved health worker performance in phenotyping and choosing correct management for reported penicillin. However, even with the AAAT, there remains a risk of potentially hazardous management choices highlighting the need for formal allergy training to expand penicillin allergy assessment services.